Evaluation of P- POSSUM Scoring System in Patients Undergoing Emergency Laparotomy - Jha, Manoj Kumar; Sibakoti, Yahun Chandra; Devkota, Harihar (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: The Physiological and Operative Severity Score for the enumeration of Mortality and morbidity (POSSUM) and its modification the Portsmouth POSSUM (P-POSSUM), have been proposed as a method for standardizing patient data so that direct comparisons can be made despite differing patterns of referral and population. In this prospective study, the validity of P-POSSUM was tested in patients undergoing emergency laparotomy and the risk factors for low outcome were noted. Methods: This is the Prospective Study and was conducted in Department of surgery, of a tertiary level hospital. The study period was from April 2014- April 2015 for one year. Patients admitted under department of general surgery scheduled to undergo emergency laparotomy were included and scored according to their physiological and operative findings using a proforma sheet. Physiological scoring was performed just before surgery and operative scoring was carried out intra-operatively. Patients were followed-up for the first 30 days postoperative period. The observed mortality rate was compared with the P-POSSUM predicted mortality rate. Data analysis was done using SPSS 20. Results: A total of 60 patients who met the inclusion criteria were included in this study. On applying linear analysis, an observed to expected ratio of 1.18 was obtained, indicating a significant fit for predicting the post-operative adverse outcome. There was no significant difference between the observed and predicted mortality rates (x2 = 1.467, 4 df., P = 0.833). It was found to be comparable to other studies. In all the risk factors studied, a positive correlation was found between deaths and higher POSSUM scores. Conclusion: Portsmouth POSSUM scoring system serves as a good predictor of post-operative outcome in emergency laparotomy procedures.